p53 wild-type colorectal cancer cells that express a fetal gene signature are associated with metastasis and poor prognosis - Laura Solé; Teresa Lobo-Jarne; Daniel Álvarez-Villanueva; Josune Alonso-Marañón; Yolanda Guillén; Marta Guix; Irene Sangrador; Catalina Rozalén; Anna Vert; Antonio Barbachano; Joan Lop; Marta Salido; et al. (Nature Communications, 2022)
The failure of chemotherapy in colorectal cancer is currently unclear. Here, the authors show that upon sub-lethal dose of chemotherapy wild-type p53 colorectal cancers acquire a quiescence-like phenotype and a YAP-dependent fetal-like intestinal stem cell state associated with a higher metastatic activity and poor prognosis in patients.